Development of Interactive E-LKPD Based on Live-Worksheets for Reading and Viewing Skills - Rizka Dwi Rahmayani; Atmazaki Atmazaki (STAI Hubbulwathan Duri, 2025)
This study addresses the need for innovative digital learning tools by developing an interactive Electronic Student Worksheet (E-LKPD) based on the Live-Worksheets platform. It aims to enhance reading and viewing skills among Phase F students (Grade XI senior high school) in Indonesian language subjects, aligning with modern educational demands for critical thinking and digital literacy. A Research and Development (RD) approach utilizing the 4-D model (Define, Design, Develop, and Disseminate) was employed. Data collection instruments included validation sheets for content, media, and language; practicality questionnaires; test instruments; and student activity observations. The E-LKPD was evaluated for validity, practicality, and effectiveness through expert reviews, small and large group trials, and assessments of students' learning outcomes and engagement. Expert validation yielded high scores for content (90%), media (86%), and language (86%). Practicality ratings were similarly high, with 89% for small groups and 91% for large groups. Students demonstrated significant learning improvements, with an average score of 92, while engagement levels reached 98%. Positive responses to the E-LKPD were reported by 91% of participants, highlighting its alignment with students' needs for interactive and creative learning. The findings confirm that the E-LKPD enhances students' reading and viewing skills, such as text comprehension and visual media analysis, while fostering a student-centered learning environment. Its integration of interactive technology promotes adaptive learning and supports digital education goals. The E-LKPD is an effective tool for improving learning outcomes and engagement, advancing literacy, and meeting the demands of digital-era education.